Increasing Student’s Motivation and Geography Learning Outcome Using Active Debate Method Assisted by ISpring Suite - Wijayanto, Pradika Adi; Utaya, Sugeng; Astina, I Komang (International Journal of Social Sciences and Management, 2017)
This research aims to know the effect of active debate method assisted by iSpring Suite on motivation and Geography learning outcome. This is a quasi-experimental research with quantitative to describe research results. Research subject is students in XI IS 1 class as the experimental group and students in XI IS 2 class as the control group in Senior High School 1 Mayong, Jepara Residence, Indonesia. Data of motivation level was collected by questionnaire, meanwhile the cognitive learning outcome data was collected by test. Based on research results it was known that: (1) there is an effect of active debate method assisted by iSpring Suite on Geography learning motivation, and (2) there is an effect of active debate method assisted by iSpring Suite on Geography learning outcome. Int. J. Soc. Sc. Manage. Vol. 4, Issue-4: 240-247